Highly Selective Recovery of Lanthanides by Using a Layered Vanadate with Acid and Radiation Resistance. Issue 5 (17th December 2019) - Sun, Haiyan; Liu, Yang; Lin, Jian; Yue, Zenghui; Li, Weian; Jin, Jiance; Sun, Qian; Ai, Yuejie; Feng, Meiling; Huang, Xiaoying
Abstract: It is of vital importance to capture lanthanides (nuclear fission products) from waste solutions for radionuclide remediation owing to their hazards. The effective separation of lanthanides are achieved by an acid/base‐stable and radiation‐resistant vanadate, namely, [Me2 NH2 ]V3 O7 (1 ). It exhibits high adsorption capacities for lanthanides ( qm Eu =161.4 mg g −1 ; qm Sm =139.2 mg g −1 ). And high adsorption capacities are maintained over a pH range of 2.0–6.9 ( qm Eu =75.1 mg g −1 at low pH of 2.5). It displays high selectivity for Eu 3+ (simulant of An 3+ ) against a large excess of interfering ions. It can efficiently separate Eu 3+ and Cs + (or Sr 2+ ) with the highest separation factor SFEu/Cs of 156 (SFEu/Sr of 134) to date. The adsorption mechanism is revealed by calculations and XPS, EXAFS, Raman, and elemental analyses. These merits combined with facile synthesis and convenient elution makes the title vanadate a promising lanthanide scavenger for environmental remediation. Abstract : The selective recovery of lanthanides is realized by a simple crystalline vanadate with acid and radiation resistance. It shows high capacities, excellent selectivity for lanthanides, and convenient elution. The adsorption mechanism is revealed by calculations and XPS, EXAFS, Raman, and elemental analysis. This supports the development of crystalline vanadates for environmental remediation.